2023
DOI: 10.3390/cancers15051423
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota of Urine, Glans and Prostate Biopsies in Patients with Prostate Cancer Reveals a Dysbiosis in the Genitourinary System

Abstract: Prostate cancer (PCa) is the most common malignant neoplasm with the highest worldwide incidence in men aged 50 years and older. Emerging evidence suggests that the microbial dysbiosis may promote chronic inflammation linked to the development of PCa. Therefore, this study aims to compare the microbiota composition and diversity in urine, glans swabs, and prostate biopsies between men with PCa and non-PCa men. Microbial communities profiling was assessed through 16S rRNA sequencing. The results indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“… 68 In this study, although we did not measure P. gingivalis -generated phosphoglycerol dihydroceramides or phosphoethanolamine dihydroceramides after infection of OSCC cells, P. gingivalis infection prevented ceramide-dependent mitophagy in both xenograft-derived human OSCC tumors and allograft-derived murine orthotopic OSCC tumors in response to LCL768 in vivo . Further, our 16S rRNA sequencing data showed an increased presence of Gordonia , 69 Stenotrophomonas , 70 , 71 , 72 , 73 and Herbaspirillum 74 , 75 in P. gingivalis- infected tumors that showed resistance to LCL768-induced mitophagy in in vivo orthotopic OSCC tumors. Whether increased levels of these bacteria in the tumor macroenvironment play any independent or synergistic roles in the modulation of lethal mitophagy in response to LCL768 in OSCC tumors is unknown.…”
Section: Discussionmentioning
confidence: 61%
“… 68 In this study, although we did not measure P. gingivalis -generated phosphoglycerol dihydroceramides or phosphoethanolamine dihydroceramides after infection of OSCC cells, P. gingivalis infection prevented ceramide-dependent mitophagy in both xenograft-derived human OSCC tumors and allograft-derived murine orthotopic OSCC tumors in response to LCL768 in vivo . Further, our 16S rRNA sequencing data showed an increased presence of Gordonia , 69 Stenotrophomonas , 70 , 71 , 72 , 73 and Herbaspirillum 74 , 75 in P. gingivalis- infected tumors that showed resistance to LCL768-induced mitophagy in in vivo orthotopic OSCC tumors. Whether increased levels of these bacteria in the tumor macroenvironment play any independent or synergistic roles in the modulation of lethal mitophagy in response to LCL768 in OSCC tumors is unknown.…”
Section: Discussionmentioning
confidence: 61%
“…It could utilize organic nutrients through fermentation metabolism and produce H 2 from peptone without utilizing carbohydrates [28]. Studies illustrated that the abundance of Genus-Peptococcus in several cancers was significantly decreased, like prostate cancer and gastric cancer, and was closely related to cancer cachexia [29][30][31]. However, so far, there is no research indicating whether there are differences in the composition and distribution of Genus-Peptococcus in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Only five out of the nine included articles, mention performing a diversity analysis. Out of those five articles, Sarkar et al, Salachan et al, and Gonçalves et al reported that their alpha diversity assessment indicated a lower species richness in samples from the malignant group than those in the benign (control) groups [38,40,41]. However, Feng et al and Cavarretta et al were not able to distinguish between benign and malignant groups with alpha or beta diversity [35,37].…”
Section: Diversity Assessmentmentioning
confidence: 99%
“…In contrast, they obtained the benign tissue controls from patients with benign prostatic hyperplasia (BPH) who underwent transurethral resection of the prostate [34,39]. Two studies used transrectal ultrasound-guided prostate biopsies to obtain tissue samples for both their benign control and experimental groups [38,41]. Only one study used mRNA-seq data downloaded from EBI ENA [36].…”
Section: Study Outcomesmentioning
confidence: 99%
See 1 more Smart Citation